Utility of high‐resolution ultrasound in measuring subcutaneous fat thickness. Issue 9 (2nd October 2022) - Anvery, Noor; Wan, Hoi Ting; Dirr, McKenzie A.; Christensen, Rachel E.; Weil, Alexandra; Raja, Sabina; Reynolds, Kelly A.; Kyllo, Rachel L.; Makin, Inder Raj S.; Poon, Emily; Alam, Murad
Abstract: Objective: Previous studies conclude that high‐resolution ultrasound (HRUS) enables noninvasive and accurate measurements of subcutaneous fat thickness. The primary objective of this cross‐sectional study was to better characterize subcutaneous fat thickness measurements in a diverse patient population using HRUS. Secondarily, we sought to correlate these measurements with patients' body image. Methods: A cross‐sectional study to measure subcutaneous fat measurements at seven distinct anatomic sites, including upper and lower extremities, submental, and torso regions, in 40 men and women of different ages and races using HRUS. Independent t ‐tests and analysis of variance were performed to analyze findings. Results: In our patient population, on average, women had thicker subcutaneous fat than men at all anatomic sites. Asian patients had significantly reduced fat thickness at peripheral anatomic sites, such as arms when compared to patients who identified as Black and Other ( p  = 0.05 and p  = 0.008, respectively). Lastly, women reported decreased total body satisfaction at all anatomic sites when compared to men. Conclusion: The information obtained and methods developed in this study may be utilized clinically during patient selection for fat reduction procedures, including for estimating the degree of likely benefit; for managing pathologies involving subcutaneous fat thickness alteration; and to monitor the progression of lipodystrophy secondary to disease or drugs.